Assessment of online pharmacy applications in India by employing the mobile application rating scale - Anum Sattar; Anum Sattar; Safila Naveed; Hina Rehman; Shahnaz Usman; Shazia Jamshed (Frontiers Media S.A., 2024)
IntroductionOver the past few years, the technology powering mobile devices such as smartphones has made significant progress. Furthermore, the healthcare industry is always progressing and actively embracing the latest technological advancements to achieve the highest level of efficiency. With the rising prevalence of smartphones and internet connection, customers are benefiting from reduced prices, convenient home delivery, and effortless accessibility through online pharmacies. Internet-based pharmacies facilitate the internet-based transaction of health-related products, such as drugs, dietary supplements, and various other wellbeing products.Objective of studyThe study assessed digital pharmacy applications in India using the Mobile App Rating Scale (MARS) on Android and iOS devices, aiming to evaluate their quality.MethodsAn investigation examined the digital pharmacy applications in India that were accessible via the Android Market and App Store. The applications were assessed by two researchers using the MARS questionnaire, a tool that evaluates 23 variables categorized into five domains: Engagement, Functionality, Aesthetics, Information, and Subjective Quality. The grading system spanned from one to five for every category.ResultsA Google Play Store and App Store investigation revealed 40 online pharmacy apps in India, with 13 rejected. Seven were non-English language-related apps and seven were not downloaded. Thirteen were chosen and evaluated using the MARS Scale. The MARS demonstrated significant positive associations across its components, namely Engagement, Functionality, Aesthetics, and Information. Specifically, greater levels of user functionality were shown to be indicative of superior app aesthetics and engagement. The mean rating of the 13 apps fell between the range of 3.11 to 4.32 on a 5-point scale.ConclusionThis is the first study to utilize the MARS scale to assess the efficacy of online pharmacy applications in India. This research enhanced the functionality and quality of various online pharmacy applications utilized in India.